Effects of Nutrient Availability on the Release of Dissolved and Particulate Organic Carbon by Pyropia haitanensis and Its Implications - Xu, Ningning; Wang, Wenlei; Xu, Yan; Ji, Dehua; Chen, Changsheng; Xie, Chaotian; Xu, Kai (Frontiers in Marine Science, 2021)
As an important component of the coastal-offshore ecosystem, Pyropia haitanensis aquaculture is continually being challenged due to rapid environmental changes because of global climate change and anthropogenic pressures. To explore the effect of nutrient availability on carbon metabolism by P. haitanensis, two strains of thalli were incubated for 15 days under four different concentrations of nitrogen and phosphorus. Significant increases in carbon, nitrogen, and phosphorus contents were observed in the algal tissue after the nitrates and phosphates enrichment, leading to elemental stoichiometry gradually approaching the Redfield ratio. Our results also showed a positive correlation between carbon or phosphorous accumulation and growth rate. Furthermore, under the natural seawater conditions, the release rates of dissolved organic carbon (DOC) and particulate organic carbon (POC) were highest, and more DOC was released than POC. The release rates tended to decrease with nutrient enrichment. The average proportions of DOC compared to total carbon were 6.3%–25.7%, while the average proportions of POC compared to total carbon were 2.1%–5.4%. Our results support the proposed importance of P. haitanensis in contributing the DOC and POC that play a significant role in the biological carbon pump and in sustaining marine aquaculture ecosystems in eutrophic environments.